Patients' and nurses' views on providing psychological support within cardiac rehabilitation programmes: a qualitative study. Issue 9 (1st September 2017) - Turner, Katrina M; Winder, Rachel; Campbell, John L; Richards, David A; Gandhi, Manish; Dickens, Chris M; Richards, Suzanne
Abstract : Objective: To explore patients' and nurses' views on the feasibility and acceptability of providing psychological care within cardiac rehabilitation services. Design: In-depth interviews analysed thematically. Participants: 18 patients and 7 cardiac nurses taking part in a pilot trial (CADENCE) of an enhanced psychological care intervention delivered within cardiac rehabilitation programmes by nurses to patients with symptoms of depression. Setting: Cardiac services based in the South West of England and the East Midlands, UK. Results: Patients and nurses viewed psychological support as central to good cardiac rehabilitation. Patients' accounts highlighted the significant and immediate adverse effect a cardiac event can have on an individual's mental well-being. They also showed that patients valued nurses attending to both their mental and physical health, and felt this was essential to their overall recovery. Nurses were committed to providing psychological support, believed it benefited patients, and advocated for this support to be delivered within cardiac rehabilitation programmes rather than within a parallel healthcare service. However, nurses were time-constrained and found it challenging to provide psychological care within their existing workloads. Conclusions: Both patients and nurses highly value psychological support being delivered within cardiac rehabilitation programmes but resource constraints raise barriers to implementation. Consideration, therefore, should be given to alternative forms of delivery which do not rely solely on nurses to enable patients to receive psychological support during cardiac rehabilitation. Trial registration number: ISCTRN34701576.